2019
DOI: 10.1108/jadee-07-2018-0088
|View full text |Cite
|
Sign up to set email alerts
|

The effects of income and food safety perception on vegetable expenditure in the Tamale Metropolis, Ghana

Abstract: Purpose The purpose of this paper is to examine how consumers’ concern for food safety and income levels influence vegetable consumption patterns and expenditure in Tamale, Ghana. Design/methodology/approach Using data from a survey of 300 urban consumers, quantile regression analyses are used to examine how food safety consciousness, income and other factors influence vegetable expenditure across different quantiles. Findings Whereas protein-rich foods take smaller proportion, vegetables and cereals take … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 51 publications
(57 reference statements)
4
25
0
Order By: Relevance
“…Being poor, rice farmers focus primarily on obtaining food (and attaining other basic needs), which constitutes higher proportions of their household expenditure. This is consistent with Amfo et al (2019), who reported that low-income households in Ghana spend 78% of their income on food. Moreover, Donkoh et al (2014) observed that food expenditure is greater than half of household expenditure of the poor in Ghana.…”
Section: Implication Of Livelihood Diversification On Consumption Expenditure Of Rice Farmerssupporting
confidence: 91%
“…Being poor, rice farmers focus primarily on obtaining food (and attaining other basic needs), which constitutes higher proportions of their household expenditure. This is consistent with Amfo et al (2019), who reported that low-income households in Ghana spend 78% of their income on food. Moreover, Donkoh et al (2014) observed that food expenditure is greater than half of household expenditure of the poor in Ghana.…”
Section: Implication Of Livelihood Diversification On Consumption Expenditure Of Rice Farmerssupporting
confidence: 91%
“…Kumar et al (2018) explored the perspective associated with the contract farming (CF) in the Nepal and effect on the farmer incomes and food safety dimensions and presented survey-based study of tomato farmers to showcase the benefits of CF and adoption of food safety practices. Amfo et al (2019) related the effect of income levels on the consumption patterns of fruits and vegetables its influences on food safety. Survey-based statistical analysis carried in urban areas of Ghana infers the strong correlation in between the income levels and food safety assessments.…”
Section: 3mentioning
confidence: 99%
“…Furthermore, contract farmers' net returns are about 38% higher than those of independent farmers, and the rate of adoption of food safety measures was found to be about 38% higher than that of independent farmers. Amfo et al (2019) investigated "the effects of income and food safety perception on vegetable expenditure in the Tamale Metropolis, Ghana", to examine how consumers' concern for food safety and income levels influence vegetable consumption patterns and expenditure. The design was a survey of 300 urban consumers.…”
Section: Empirical Reviewmentioning
confidence: 99%